Implementation of Web-Based Geographical Information System Mapping Recipients of Social Assistance in Giri Purno Village - Dwi Winarti; Lido Sabda Lesmana; Tias Pratiwi (Komunitas Dosen Indonesia, 2023)
Giri Purno Village is a village located in Rimbo Ilir District, Kab. Tebo. This village is one of the villages that receives social assistance from the government where the assistance will be passed on to people in need. The distribution of the location of the houses that receive assistance is still not available, so the coordinates of the houses receiving social assistance are needed. Therefore, we need a geographic information system in which the system contains information and the distribution of the location of houses that receive social assistance. This information system uses the Laravel framework, Laravel is a PHP framework for building a web-based system framework and uses the leafletjs library as a tool for displaying maps and Open Street Map as the base map used. The research method used is the waterfall method. The waterfall method is the earliest SDLC approach used for software development. This research resulted in a Geographic Information System that is capable of managing social assistance beneficiary data, RT data, social assistance beneficiary criteria and can visualize social assistance beneficiary location points on maps spread across Giri Purno Village. In addition, there are also details of recipients of social assistance as well as the route to the recipient's house.